2016
DOI: 10.1186/s12885-016-2328-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism rs3760396 of the chemokine (C-C motif) ligand 2 gene (CCL2) associated with the susceptibility of lung cancer in a pathological subtype-specific manner in Han-ancestry Chinese: a case control study

Abstract: BackgroundChemokines are well known inflammatory factors critical for tumor development in diverse tissues, including lung cancer. Chemokine (C-C motif) Ligand 2 (CCL2) was one of such chemokines important for both primary tumor development and metastasis of various cancers. Polymorphism at rs3760396 of CCL2 genes is associated with the prognosis of non-small cell lung cancer (NSCLC). The goal of our study was to examine the relationship of genetic polymorphisms rs3760396 with the susceptibility of lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…42,43 The chemokine CCL2 has been identified to be an important characteristic substance in many human cancers such as breast cancer, 44 ovarian cancer, 45 and lung cancer. 46 According to previous researches, the polymorphisms of CCL2 and its receptors are related to the transitional bladder cell carcinoma. 47,48 A few studies have also reported that CCL2 is a key contributor in mediating the migration and invasion of BC cells in the signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 The chemokine CCL2 has been identified to be an important characteristic substance in many human cancers such as breast cancer, 44 ovarian cancer, 45 and lung cancer. 46 According to previous researches, the polymorphisms of CCL2 and its receptors are related to the transitional bladder cell carcinoma. 47,48 A few studies have also reported that CCL2 is a key contributor in mediating the migration and invasion of BC cells in the signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Rs1024611 seats on positions -2518 in MCP-1 5'-flnking region with the allele mutation of A to G, and affects MCP-1 transcription activity [15]. Rs3760396 is confirmed as a deleterious mutation in the Chinese Han population, and has been reported to be correlated with lung cancer [16]. However, their genetic association with AMD risk in the Chinese Han population has been unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between the average expression level of this gene in the cancer samples and its average expression level in the normal samples was as large as 1678.72, whereas the average of the corresponding differences for all the DE genes identified by SAM was only 245.03. It has been reported that this gene may play an important role in the development of lung cancer29. For another example, the average expression level of TNFAIP3 was ranked at the top 7.4% and 3.2% of all the measured genes in the cancer and normal samples, respectively.…”
Section: Resultsmentioning
confidence: 99%